Dietary Intake and Energy Expenditure Assessed during a Pre-Season Period in Elite Gaelic Football Players - O’Brien, Luke (Sports (Basel), 2019)
There is currently a lack of research into the energy demands and associated nutritional intakes of elite Gaelic football players during the pre-season period, which is a crucial time of year for physical development. The aim of the current study was to investigate the dietary intake and energy expenditure (EE) of elite Gaelic football players during a typical pre-season week. Over a seven-day period, which included four training days and three rest days, dietary intake (validated self-reported estimated food diary) and EE (Sensewear Pro armband) were recorded in 18 male players from a single elite inter-county Gaelic football team. Average energy intake (EI) (3283 ± 483 kcal) was significantly (p = 0.002) less than average EE (3743 ± 335 kcal), with a mean daily energy deficit of −460 ± 503 kcal. Training days elicited the greatest deficits between intake and expenditure. The mean carbohydrate (CHO) intake was 3.6 ± 0.7 g/kg/day, protein intake was 2.1 ± 0.5 g/kg/day, and fat intake was 1.6 ± 0.2 g/kg/day. These findings indicate that the dietary practices of the sampled players were inadequate to meet EE and CHO recommendations. Training days are of particular concern, with the players not altering energy and CHO intake to encounter increased energy demands. Education on nutritional strategies for elite Gaelic footballers should be considered in relation to training demands to avoid detriments to performance and health.